Pharmacy Students’ Readiness for Offline Learning in The New Normal Transmission of COVID-19: A Cross-Sectional Study - Budi Suprapti; Dinda Monika Nusantara Ratri; Mareta Rindang Andarsari; Fany Devita Ritonga; R.R. Endang Lukitaningsih; Enda Mora; Enok Nurliawati (Universitas Airlangga, 2024)
Background: Pharmacy students consist of undergraduate and professional pharmacy students. They are candidates for future pharmacist health workers who require practical experience. Offline learning with hands-on practice methods in health facilities supports their professional skills. Objective: This study aimed to determine pharmacy students' knowledge and attitude toward implementing offline learning methods during the new normal era. Methods: This study involved pharmacy students from Indonesia who were asked to participate in an e-questionnaire about the vaccination program, COVID-19 health protocols, pharmacist competence, and attitude toward implementing offline learning. The students' scores were based on their knowledge and attitude. Statistical analysis was performed to compare the scores between the two groups, and a correlation test was conducted to assess the relationship between the students' knowledge and attitudes. Results: A total of 652 pharmacy students were divided into two groups, undergraduate and professional pharmacy students, in a 3:1 ratio. About 74.6% of undergraduate students and 78.5% of professional pharmacy students had good and moderate knowledge. The level of knowledge was not different between the two groups (p=0.602; p>α). Professional pharmacy students were more ready to engage in offline learning compared to undergraduate students (p=0.001; p<α). However, there was a relatively low correlation between knowledge and attitudes, with r = 0.079 (p=0.043; p<α). Conclusion: Professional pharmacy students are more ready for offline learning methods than undergraduate students, particularly in hands-on field practice.